Prevalence of Chronic Gingivitis Among 16 Years Old Public High School Students in Khartoum (Med Phoenix, 2018)
Background: This study was designed to measure the prevalence of chronic gingivitis among 16- year-old public high school students in Khartoum State.Methods: A total of 385 high school students of 16 years of age, from public schools in different geographical locations representing different socioeconomic classes in Khartoum were randomly selected and examined. The variables of the present study had been collected by one examiner using a direct interview questionnaire and all the present teeth were examined at four sites (Mesiobuccal, distobuccal, mesiolingual, distolingual) for the presence of plaque, using the Plaque Index (Loe and Sillness) and Gingival Index (Sillness and Loe).Results: Prevalence of gingivitis was 96.9%, of which 68.6% were of mild form (majority), 27.5% of moderate condition and only 0.8% was of severe grade. The most common form of gingivitis was the generalized form that accounted for 94.5%. The relationship between oral hygiene and degree of gingivitis was assessed after collecting data on study area, gender, socio-economic status, tooth brushing tool used, frequency of brushing per day, direction of tooth-brushing and regularity of dental visits. The adjusted relationship was still significant at the 99% confidence level (p-value 0.000), with a correlation coefficient of 0.704.Conclusions: The study showed significantly higher prevalence of chronic gingivitis among 16-year-old public high school students in Khartoum State. The degree of gingivitis showed statistical significance when correlated with oral hygiene status, socioeconomic status, frequency and horizontal direction of tooth brushing, while it showed insignificance when correlated with gender. Med Phoenix. Vol. 3, Issue. 1, 2018, Page : 1-5